Method for producing a corrosion-resistant aluminum-silicon alloy casting, such a corrosion-resistant aluminum-silicon alloy casting and its use - Patents.com
A multi-stage anodization process for aluminum-silicon alloys addresses the issue of non-uniform oxide films by creating a dense, thicker film with reduced zero spots, improving corrosion resistance and efficiency.
Patent Information
- Application Number
- JP2021546822
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-15
- Filing Date
- 2020-02-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-02-13
AI Technical Summary
Existing anodizing methods struggle to produce a uniform aluminum oxide film on aluminum-silicon alloys due to silicon's inert nature, leading to areas without oxide formation and increased pitting corrosion.
A multi-stage anodization process involving a first pre-anodization stage at 1-40V and a second anodization stage at 20-50V, combined with specific acid treatments and sealing processes, to create a uniform and thicker aluminum oxide film.
The method results in a denser, thicker aluminum oxide film with reduced zero spots, enhancing corrosion resistance and reducing processing time by up to 80%, while maintaining aesthetic appeal.
Smart Images

Figure 0007621260000007 
Figure 0007621260000008 
Figure 0007621260000009
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of metal surface production by anodizing, and more particularly to a method for producing corrosion-resistant aluminum-silicon alloy castings, and more particularly to the optimization of anodized cast aluminum parts with high silicon content using multiple anodizing cycles.Furthermore, the present invention relates to a corrosion-resistant aluminum-silicon alloy casting and its uses. [Background technology]
[0002] Today, aluminum is finding new applications in new industries, especially in the automotive industry, due to its excellent strength-to-weight ratio. Automotive companies, which are looking to reduce weight to reduce greenhouse gas emissions, tend to use aluminum alloys. Furthermore, weight reduction is one of the key goals for electric mobility, which is strongly limited by the capacity of current batteries. To overcome the short driving range of electric vehicles due to current battery technology, weight reduction is the key to overcoming this obstacle.
[0003] Cast aluminum alloys, rich in intermetallic compounds, are one of the most used types, especially in automotive applications replacing steel parts. However, aluminum, like all other metals, is susceptible to corrosion, especially pitting corrosion, in the presence of aggressive ions. Intermetallic compounds act as galvanic couples under the oxide film and initiate the pitting phenomenon. Thus, pitting and other forms of localized corrosion are real problems for cast alloys due to their segregation structures and alloying element contents of various chemical compositions.
[0004] Among the most effective and common methods to improve the corrosion resistance of aluminum is the "anodizing" method, which increases the thickness of the oxide layer on aluminum. Anodizing is an electrochemical method that is mainly applied to aluminum, magnesium and titanium. In this method, the thickness of the native oxide film on the base metal is increased, improving the surface properties. The concept of anodizing relies on the application of an anodic potential to the substrate, thus favoring the dissolution of the surface. However, the applied potential shifts the reference potential on the surface towards passivation, thus creating a favorable environment for the oxide film to grow.
[0005] One of the biggest challenges in anodizing is the content of foreign matter, i.e. alloying elements. During the dissolution of aluminum, they tend to interrupt the process. One of the alloying elements that most adversely affects the anodizing efficiency and quality is the silicon content. Due to its inert and low conductive nature, silicon acts like a barrier on the substrate surface and prevents the growth of oxides. This problem becomes especially strong in high silicon alloys, where silicon is added for increased castability with the die casting process. Due to its relatively inert nature, silicon prevents aluminum oxide from growing, thereby creating areas without anodized film and also limiting the thickness of the oxide film. Once the process is finished, these empty zones with a silicon secondary phase in the center create cathodic zones in the discontinuous anodized film, enhancing the problem of pitting corrosion during the service life.
[0006] EP1774067B1 discloses a method and composition for anodizing, by micro-arc oxidation, in particular of magnesium, magnesium alloys, aluminum, aluminum alloys or mixtures thereof, or surfaces or mixtures of surfaces containing such metallic materials. This patent does not address the problem of pitting corrosion and the method for obtaining a uniform oxide film.
[0007] WO 2017 / 089687 discloses a method for the continuous processing of aluminum alloy strip, which includes forming a chemical conversion coating on the surface of the strip by reaction with a chemical conversion treatment agent. This document teaches the use of additional different metals to form the coating on the surface of the aluminum alloy, which creates additional costs.
[0008] LE Fratila-Apachitei et al. 2003 reported the use of different current waveforms (i.e., square wave, ramp square wave, ramp-down and ramp-down spike) to investigate the effect of ion implantation on Al, AlSi 10 and AlSi 10 Different techniques for the anodization of Cu3 have been disclosed.
[0009] None of these prior art documents discloses a method for obtaining a uniform aluminum oxide film capable of protecting against corrosion problems. Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, the problem posed by the present invention was to provide an aluminum alloy substrate having improved corrosion resistance. [Means for solving the problem]
[0011] This problem is solved by a method for producing a corrosion-resistant aluminium-silicon alloy casting having the features of claim 1 and by a corrosion-resistant aluminium-silicon casting having the features of claim 8. Claim 17 provides a use of the corrosion-resistant casting. The further dependent claims represent preferred embodiments.
[0012] Corrosion-resistant aluminum-silicon alloy substrates are provided having a uniform aluminum oxide coating with an average thickness of 4-90 μm as a corrosion protection layer. Aluminum-silicon alloys in the context of the present invention contain aluminum and silicon, but may also contain further metals such as magnesium, iron, manganese, titanium, copper, chromium, zinc, tin, nickel, lead, silver, beryllium, bismuth, lithium, cadmium, zirconium, vanadium, scandium, and combinations thereof. Additionally, the alloys may contain up to 0.1% by weight of other impurities.
[0013] To solve this problem, the present invention proposes a method for producing corrosion-resistant aluminum-silicon alloy castings, which comprises the following steps: a) providing an aluminum-silicon alloy casting; and b) growing at least partially a corrosion protection layer on the surface of said aluminum-silicon alloy casting using a multi-step anodizing method comprising the steps of b1) and b2) below: b1) a first stage of pre-anodizing for oxidizing aluminum on the surface of the casting at a voltage of 1 to 40 V; b2) A second anodizing step for oxidizing the aluminum and silicon on the surface of the casting at a voltage of 20-50V.
[0014] The voltage of the second anodization step of the method is higher than the voltage of the first pre-anodization step. Effect of the Invention
[0015] By using this technique, the coatings are thicker and the process can be shortened by up to 80 percent due to the activation of secondary silicon phases, which act as inhibitors that slow down or stop oxidation in classical anodization, which leads to shorter processing times by using this technique.
[0016] Also, the denser and thicker film combined with the sealing layer provides not only better corrosion resistance but also a more uniform layer, which is more aesthetically pleasing without zero spots. Zero spots are zones of the aluminum alloy that have no aluminum oxide film on the surface after anodization. These spots are caused by the presence of silicon intermetallic compounds in the aluminum alloy that do not oxidize at the low voltages more suitable for aluminum. [Brief description of the drawings]
[0017] [Figure 1] In Figure 1, OM 200 X-section images of a surface produced by classical anodizing (Figure 1a) and a surface obtained using two-stage anodizing (Figure 1b) are shown. On the surface of the sample produced by classical anodizing (Figure 1a), zero spots can be seen. However, on the surface of the sample (Figure 1b) obtained using two-stage anodizing, a uniform anodic oxide layer without zero spots can be seen. A high silicon concentration can locally prevent the formation of anodic oxide. Zones not covered by an oxide layer with zero spots do not affect the coating properties, which is only possible with a minimum oxide coverage of 85%. [Diagram 2] Figure 2 shows SEM SEI 500X cross-sectional images of sample A as a control group (Figure 2a), sample B anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 2b), sample C pretreated for 4 min and anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 2c), and sample D pretreated for 10 min and anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 2d). [Diagram 3] Figure 3 shows SEM SEI 500X surface images of sample A as a control group (Figure 3a), sample B anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 3b), sample C pretreated for 4 minutes and anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 3c), and sample D pretreated for 10 minutes and anodized with sulfuric acid and a proprietary organic anodizing additive (Figure 3d). [Figure 4] In FIG. 4 the NSS results of samples A, B, C and D after being subjected to 480 hours of NSS according to ISO 9227 are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In a more particular embodiment of the invention, the voltage applied during the first stage is between 5 and 30 V, preferably between 10 and 20 V, and preferably the duration of the first stage is between 2 and 8 minutes. This first stage is preferably carried out at a temperature between 1 and 50°C, more preferably between 5 and 30°C, and most preferably between 10 and 20°C.
[0019] In a more particular embodiment of the invention, the voltage applied during the second stage is between 25 and 40 V, and preferably the duration of the second stage is between 2 and 20 minutes. This second stage is preferably carried out at a temperature between 1 and 50°C, more preferably between 5 and 30°C, and most preferably between 10 and 20°C.
[0020] In a more particular embodiment of the present invention, these two stages are carried out in acid baths containing different organic additives. In other words, the bath remains the same in these two stages, i.e. the vessel in which the bath resides remains the same, despite the difference in organic additives. The process of this embodiment saves time and costs, since there is no need to prepare two different baths (vessels) on the industrial line.
[0021] In a more particular embodiment of the invention, the acid bath comprises sulfuric acid, the concentration of sulfuric acid in the bath being preferably between 50 g / L and 250 g / L, more preferably between 100 g / L and 200 g / L, and most preferably between 150 g / L and 190 g / L.
[0022] In another embodiment of the invention, the first stage of pre-anodizing is preceded by a desmutting step in which the aluminum alloy is exposed to an acid. Desmutting is a chemical action to remove pre-treatment residues (smuts) resulting from attack of the alloy intermetallic species without necessarily significantly attacking the aluminum itself.
[0023] In a more particular embodiment of the present invention, said acid is selected from the group consisting of nitric acid, phosphoric acid, sulfuric acid, fluoride containing acidic media, and any organic acid, combinations thereof not limited to any catalyst such as hydrogen peroxide or persulfates or ferric sulfate.
[0024] In a more particular embodiment of the present invention, the duration of the desmutting step is from 0.1 to 40 minutes, preferably from 0.5 to 20 minutes, more preferably from 0.8 to 10 minutes.
[0025] In another embodiment of the present invention, the desmutting step is preceded by an acid pretreatment step which comprises contacting the aluminum alloy with an acid. The time period for the acid pretreatment step is preferably 1 to 40 minutes, more preferably 2 to 20 minutes, and most preferably 3 to 10 minutes. The acid pretreatment step is preferably carried out at a temperature of 60 to 120°C, more preferably 70 to 100°C, and most preferably 80 to 95°C.
[0026] In a more particular embodiment of the present invention, said acid pretreatment step is carried out at a pH of less than 6, preferably less than 4, more preferably less than 2.
[0027] In another embodiment of the present invention, the acid pretreatment step is preceded by a degreasing step in which the aluminum alloy is exposed to a cleaning agent. The cleaning agent is preferably an alkaline, acidic or solvent-based cleaning agent, more preferably an acid-based cleaning agent. The duration of the degreasing step is preferably 1-40 minutes, more preferably 2-20 minutes, most preferably 3-15 minutes. Furthermore, the degreasing step is preferably carried out at a temperature of 30-80°C, more preferably 40-70°C, most preferably 50-65°C.
[0028] In another embodiment of the invention, the second step of anodization is followed by a sealing treatment comprising at least one of the following sealing treatments A), B) and C): A) Hot seal, in which the anodized aluminum-silicon alloy casting is exposed to water at a temperature of 90-100° C. and / or at least one surfactant to remove smut. B) Medium temperature seal, in which the anodized aluminum-silicon alloy casting is exposed to any organic agent or metal salt, such as nickel acetate or magnesium acetate, to improve the seal quality. C) Cold seal, which includes the following steps: 1. a first step of cold sealing, in which the anodized aluminum-silicon alloy casting is exposed to metal salts selected from the group of nickel salts and / or magnesium salts and / or chromium salts and / or zirconium salts, preferably nickel fluorides and / or nickel acetate and / or trivalent chromium and / or zirconium salts and / or magnesium acetate and / or lithium hydroxide, more preferably nickel fluorides and / or nickel acetate, and at least one surfactant; and 2. A second aging step in which the anodized aluminum-silicon alloy casting is exposed to deionized water or at least one surfactant to remove any smut that has formed on the surface.
[0029] In a more specific embodiment of the present invention, the duration of hot sealing is 10 to 50 minutes, preferably 20 to 40 minutes, more preferably 25 to 35 minutes. The hot sealing is preferably carried out at a temperature of 80 to 130° C., more preferably 85 to 120° C., most preferably 90 to 110° C. Preferably, the hot sealing is carried out at a pH of 4 to 7, more preferably 5 to 6.5.
[0030] In a more particular embodiment of the invention, the duration of the first cold seal step is between 5 and 40 minutes, preferably between 10 and 30 minutes, more preferably between 15 and 25 minutes. The first cold seal step is preferably carried out at a temperature between 10 and 50° C., more preferably between 15 and 40° C., most preferably between 20 and 30° C. The first cold seal step is preferably carried out at a pH between 5 and 7, more preferably between 5.5 and 6.5.
[0031] In a more specific embodiment of the present invention, the duration of the aging step (second step) is from 1 to 30 minutes, preferably from 2 to 20 minutes, more preferably from 5 to 15 minutes, and the aging step is preferably carried out at a temperature of from 50 to 100°C, more preferably from 60 to 90°C, and most preferably from 65 to 85°C.
[0032] In a preferred embodiment of the invention, said aluminum oxide film is obtained by a multi-step anodization process comprising at least one, and more preferably all, of the following steps: a) Degreasing process; b) an acid pretreatment step; c) desmutting step; d) a pre-anodizing step for oxidizing the aluminum on the surface of the casting at a voltage of 1 to 40 V; e) a second anodization step for oxidizing aluminum and silicon on the surface of the casting at a voltage of 20 to 50 V, the voltage of the second anodization step of the method being higher than the voltage of the first step of pre-anodization, f) a cold seal process; and g) Aging process.
[0033] Furthermore, the present invention provides a corrosion-resistant aluminum-silicon alloy casting having an aluminum oxide coating having an average thickness of 4 to 90 μm as a corrosion protection layer.
[0034] The percentage of zero spots was determined by measuring the surface area of 1 cm of aluminum oxide using an optical microscope. 2 The surface of the zero spots is then determined and the percentage of the zero spots compared to the total surface observed is obtained.
[0035] Additionally, by using pre-anodization and reducing the general electrical conductivity, the risk of electrical breakdown at higher current densities is also reduced, increasing productivity and reducing rework percentages.
[0036] In a more specific embodiment of the present invention, the aluminum oxide film has an average thickness of 1 to 90 μm, preferably 5 to 70 μm, more preferably 10 to 50 μm.
[0037] The coating thickness is determined in accordance with DIN EN ISO 1463. This average coating thickness is calculated over an appropriate number of measuring points on the cross section. At least three local individual measured values on the cross section must be used for each measuring point.
[0038] In a more particular embodiment of the present invention, the aluminum oxide film has a ratio of average maximum coating thickness to average minimum coating thickness of 8:1, preferably a ratio of 6:1, and more preferably a ratio of 4:1.
[0039] This ratio is calculated by taking a 300 μm cross section with SEM 250X. Then, the three points with the largest coating thickness and the three points with the smallest coating thickness are determined and their thicknesses are measured. The average maximum coating thickness and the average minimum coating thickness can then be calculated.
[0040] In a more particular embodiment, the surface of the substrate is substantially free of zero spots, meaning that the coverage of the surface by oxide is greater than 88%, preferably greater than 92%, more preferably there are no zero spots at all, the zero spots preferably having a maximum width of 60 μm.
[0041] The coverage and zero spot measurements are determined according to norm TL 212 published 2016-12 by Volkswagen. The coverage of the surface is determined by the percentage of the measured length inspected. The zero point width in the microsection must not exceed 60 μm.
[0042] In a more particular embodiment of the invention, said aluminium oxide film has a maximum pure silicon concentration of 5% by weight, preferably between 0.5 and 2% by weight.
[0043] In a more particular embodiment of the present invention, the Si-O to Si ratio in said aluminum oxide film is not less than 60%.
[0044] In a more particular implementation of the invention, the corrosion resistant aluminum-silicon alloy casting (i.e. the casting coated with an aluminum oxide film) can be characterized by its L, a, b values obtained using optical spectrophotometry, which are comprised between 49 and 65 for L, between -0.7 and -0.1 for a, between 1.7 and 4 for b, and preferably between 52 and 60 for L, between -0.5 and -0.3 for a, and between 1.8 and 3.8 for b.
[0045] The L, a, b values are determined in accordance with BS EN ISO 6719 and BN EN ISO 11664-4.
[0046] In a more particular embodiment of the present invention, said aluminum alloy comprises 0.5-70% by weight, preferably 5-20% by weight, more preferably 6-15% by weight of silicon.
[0047] In a more particular embodiment of the present invention, said aluminum alloy comprises an additional metal selected from the group consisting of magnesium, iron, manganese, titanium, copper, chromium, zinc, tin, nickel, lead, silver, beryllium, bismuth, lithium, cadmium, zirconium, vanadium, scandium, and combinations thereof, preferably an additional metal selected from the group consisting of magnesium, iron, manganese, titanium, copper, chromium, more preferably magnesium, iron.
[0048] In a more particular embodiment of the present invention, the aluminum alloy is selected from the group consisting of AlSi7Mg alloy, AlSi 10 Alloys and AlSi 12(Fe) alloy.
[0049] The corrosion resistant aluminium-silicon alloy casting is preferably obtained by the method as described above.
[0050] With reference to the following figures and examples, the subject matter according to the invention is intended to be explained in more detail, without wishing to limit the subject matter to the specific embodiments shown therein. EXAMPLES
[0051] 1. Sample Preparation Cast aluminum alloy AlSi7Mg, AlSi 10 and AlSi 12 The (Fe) samples were cut to a size of 5X5 inches and degreased using standard proprietary chemicals available in the industry. The first set of samples were anodized using direct current in acid-based baths containing different organic additives.
[0052] Degreasing is carried out in Alumal Clean 118 L based on 40 g / L cleaning surfactant. Acid pretreatment is carried out, for example, with 100% pure phosphoric acid (concentrated). Desmutting is carried out in nitric acid at 250 g / L. The acid bath for anodization consists of sulfuric acid at a concentration of 200 g / l and the organic additive Alumal Elox 557 at a concentration of 30 g / l.
[0053] After anodization, only the samples selected for NSS testing were stained black at 66°C for 15 minutes. Samples for surface investigation studies were placed directly on nickel fluoride at a concentration of 6 g / l and pH=5.9, and subjected to a cold seal treatment followed by a warm rinse bath with deionized water having a conductivity of 25 microSiemens. Results were repeated three times to show reproducibility.
[0054] Finally, another acid pretreatment was performed to improve the properties of the aluminum oxide film.
[0055] The aluminum oxide films were characterized using optical microscopy (OM), scanning electron microscopy / energy dispersive spectroscopy (SEM / EDS), spectrophotometry, and XPS. The corrosion resistance was tested using Natural Salt Spray (NSS).
[0056] The L, a, and b values were measured using a Shimadzu UV-2600 spectrometer, and the measurement wavelength was 220 to 1400 nm. Then, the color values of the object to be measured were calculated from the spectrum obtained by the spectrophotometer using software (COL-UVPC color measurement software).
[0057] To show the negative effect of silicon intermetallic compounds, standard anodized samples were investigated by OM and SEM / EDS under polarized light. For cross-sectional examination, the samples were cut with a precision cutter, polished and finally molded in low-temperature resin. For cross-sectional SEM studies, the prepared samples were sputtered with Au for at least 20 s to prevent charge accumulation. Finally, NSS was applied to all black-stained parts for up to 480 h according to the ISO 9227:2017 standard and the first onset of corrosion and color fading were reported.
[0058] The various conditions used for the above samples are listed in Tables 1-3 below.
[0059] [Table 1]
[0060] [Table 2]
[0061] [Table 3]
[0062] 2. Sample Characteristics Sample A is used as a control and is compared with samples B, C and D. The aluminum oxide films were characterized using SEM cross-section and surface analysis, as shown in Figures 2 and 3.
[0063] Figures 2a) and 3a) are the results of a classical anodization process belonging to sample A. Due to the detrimental effect of the relatively inert nature of Si, the aluminum oxide film growth on the high silicon content zones is weakened, which results in a discontinuous and very thin (up to 0.15-0.2 mil) oxide layer.
[0064] Using a two-step anodization method, the second set of samples, Sample B, was fabricated using the same parameters as the control group Sample A. As can be seen in Figure 2b) compared to Figure 2a), the oxide growth has a higher thickness up to 0.47 mils. Furthermore, the increased thickness also works against the inhibitory effect of silicon intermetallics, resulting in a continuous aluminum oxide film, where silicon secondary phases are trapped in / on the oxide film, as can be seen from the surface SEM image in Figure 3b).
[0065] Said pretreatment makes it possible to further improve the thickness of the oxide layer from 0.98 mil to 1.37 mil, with a denser coating on the surface, as can be seen in Figures 2c) and d). These surface images also show an enhanced continuity of the layer, with silicon particles mostly embedded in the aluminum oxide film, showing much fewer cracks than sample B in Figure 3b). Comparing the images from Figures 2 and 3 for samples C and D, where the pretreatment time was increased from 4 to 10 minutes, no significant improvement in the thickness and / or integrity of the layer was observed. However, looking at the surface image from Figure 3, it can be said that the choice of 10 minutes gives a smoother appearance, due to the brightening effect of the pretreatment.
[0066] Samples B, F, J, K, L, N, O, R, V, W, Y were used to measure the L, a, b values of the aluminium castings obtained by this method, these values can be found in Tables 4 and 5 below for the colour obtained for each sample.
[0067] [Table 4]
[0068] [Table 5]
[0069] The final color of the cast aluminum oxide layer depends on the luster and color of the base metal. The color of the transparent anodization is the main condition for obtaining a durable and aesthetically appealing final color. A color comparison of classically anodized and two-stage anodized samples is shown in Table 5. The samples were anodized using different anodization parameters and stained in inorganic gold dye. A brighter and more transparent color can be obtained by using two-stage anodization.
[0070] 3. Assessment of corrosion resistance To determine the contribution of different surface treatments to corrosion resistance, corrosion resistant samples were subjected to the NSS test. The above samples were dyed black so that the corrosion spots could be seen more clearly and also the effect of this test on color fading could be observed.
[0071] The results from the NSS tests (shown in Table 6) are consistent with the SEM observations, and the best corrosion behavior was achieved, as expected, for samples C and D. For sample B, no signs of corrosion were detected, but the presence of discoloration indicated that the oxide film thickness plays an important role for the color integrity.
[0072] [Table 6]
[0073] Due to the good performance of samples C and D after 480 hours of NSS, larger area samples were produced to repeat the tests to see where the first signs of corrosion and / or discoloration would begin.
Claims
1. The following steps: a) providing an aluminum-silicon alloy casting; and b) The following b1) and b2): b1) a first stage of pre-anodization for oxidizing the aluminum on the surface of the casting at a voltage of 1 to 30 V; wherein the duration of the first stage is 2 to 8 minutes, and the voltage is kept constant during the first stage of pre-anodization; b2) a second anodizing step for oxidizing the aluminum and silicon on the surface of the casting at a voltage of 20 to 50 V; wherein the duration of the second anodizing step is 2 to 20 minutes, and the voltage is kept constant during the second anodizing step. growing a corrosion protection layer at least partially on the surface of said aluminum-silicon alloy casting using a multi-step anodizing process comprising: wherein the voltage of said second anodization stage b2) is higher than the voltage of said first stage b1) of pre-anodization; These two stages are carried out in an acid bath containing sulfuric acid, the concentration of which is between 50 and 250 g / L; the acid bath comprises an organic additive selected from the group consisting of oxalic acid, tartaric acid, glycolic acid, ethylene glycol, and combinations thereof; The present invention relates to a method for producing a corrosion-resistant aluminum-silicon alloy casting.
2. 2. The method according to claim 1, characterized in that the voltage applied during the first step b1) is between 5 and 30 V and / or the voltage applied during the second step b2) is between 25 and 40 V.
3. 3. The method according to claim 2, characterized in that the voltage applied during the first step b1) is between 10 and 20V.
4. 4. The method according to claim 1, wherein the first step b1) is carried out at a temperature of 1 to 50° C. and / or the second step b2) is carried out at a temperature of 1 to 50° C.
5. 4. The method according to claim 1, wherein the first step b1) is carried out at a temperature of from 5 to 30° C. and / or the second step b2) is carried out at a temperature of from 5 to 30° C.
6. 4. The method according to claim 1, wherein the first step b1) is carried out at a temperature of 10 to 20° C. and / or the second step b2) is carried out at a temperature of 10 to 20° C.
7. The method according to claim 1, characterized in that the concentration of the sulfuric acid is 100 to 200 g / L.
8. At least one of the following pretreatment steps: a) a desmutting step of exposing the aluminum-silicon alloy casting to an acid; b) exposing the aluminum-silicon alloy casting to an acid pretreatment step; c) a degreasing step of exposing the aluminum-silicon alloy casting to a cleaning agent; 8. The method according to claim 1, wherein a step b1) of pre-anodization is carried out prior to said first step b1).
9. 9. The method of claim 8, wherein the acid is selected from the group consisting of nitric acid, phosphoric acid, sulfuric acid, fluoride-containing acidic medium and any organic acid, the combination of which is not limited to any catalyst.
10. The second anodization step b2) is followed by a sealing step, which comprises the following steps: a) hot sealing the anodized aluminum alloy by exposing it to water and / or surfactants at temperatures between 90-100°C to remove smut; b) a medium temperature seal in which the anodized aluminum alloy is exposed to an optional organic agent or metal salt to improve the seal quality; c) a cold seal process comprising a first sealing step of exposing the anodized aluminum alloy casting to a metal salt selected from the group consisting of nickel salts and / or magnesium salts and / or chromium salts and / or zirconium salts and at least one surfactant, and a second aging step of exposing the anodized aluminum alloy casting to deionized water and / or at least one surfactant to remove smut formed on the surface.
10. The method according to claim 1, wherein the method is selected from one of the following:
11. 11. The method according to claim 10, wherein the metal salt is selected from the group of nickel fluoride and / or nickel acetate and / or trivalent chromium and / or zirconium salts and / or magnesium acetate and / or lithium hydroxide, more preferably nickel fluoride and / or nickel acetate.
Citation Information
Patent Citations
JP1971013127Y1
JP1975112234A
Formation of anodically oxidized film on aluminum alloy part
JP1995126891A
Surface treatment of vacuum chamber member made of aluminium or aluminum alloy
JP1996144088A
Piston for internal combustion engine and surface treating method therefor
JP2000027993A